PENERAPAN E-LKPD LIVE WORKSHEETS BERBASIS MODEL INKUIRI TERBIMBING TERHADAP PENINGKATAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Umatullaila Istiqfarin; Hasan Subekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking skills are an important 21st century competency that needs to be developed, but are still low in junior high school students. This study aims to describe the implementation of learning and the improvement of critical thinking skills. The method used is a quantitative approach with a pre-experimental design of the One Group Pretest-Posttest type. A total of 32 students of class VII A at a private junior high school in Surabaya were selected as research participants using a purposive sampling technique. The data collection instrument was a critical thinking ability test sheet containing 10 descriptive questions on the theme of water pollution. Data processing was carried out through the Shapiro-Wilk normality test, the Paired Sample T-Test, and the calculation of the N-gain score. The research findings showed that there was a significant difference between the scores before and after the intervention, with a significance value of 0.000 (below the threshold of 0.05). The N-gain value obtained was 0.60 indicating an increase in the moderate category. Based on these findings, it can be concluded that the combination of the guided inquiry model and E-LKPD Live Worksheets positively contributes to the development of students' critical thinking skills.